Outcomes following synchronous liver resection, cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for colorectal liver and peritoneal metastases: A bi-institutional study. (June 2021) - Flood, Michael P.; Waters, Peadar S.; Kelly, Michael E.; Shields, Conor; Conneely, John; Ramsay, Robert; Michael, Michael; Loveday, Benjamin; Warrier, Satish K.; Mulsow, Jurgen; Heriot, Alexander G.
Abstract: Purpose: Synchronous liver resection, cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) for colorectal liver (CRLM) and peritoneal metastases (CRPM) has traditionally been contraindicated. However, latest practice promotes specialist, multidisciplinary-led consideration for select patients. This study aimed to evaluate the perioperative and oncological outcomes of synchronous resection in the management of CRLM and CRPM from two tertiary referral centres. Method: This bi-institutional, retrospective, cohort study included patients undergoing simultaneous liver resection, CRS and HIPEC for metastatic colorectal cancer from 2013 to 2020. Patients treated with ablative liver techniques, staged operative approaches and extra abdominal disease were excluded. Overall survival (OS) and disease-free survival (DFS) rates were assessed. Univariate and multivariate analyses identified variables associated with survival and major morbidity (Clavien-Dindo grade III/IV). Results: Twenty-three patients were included. The median peritoneal carcinomatosis index (PCI) was 9 (range 0–22). There were two major liver resections and 21 minor resections. CC-0 resections were achieved in all patients. Major morbidity occurred in 7 patients. There were no deaths at 90 days. PCI was independently associated with morbidity (p = 0.04). PCI >10 (p = 0.069), major morbidity (p = 0.083) and presence of KRAS mutation (p = 0.052) approached significance for poor OS. Median follow up was 21 months (4–54 months). Median OS was 37 months, 3-year survival 54%, and median DFS 18 months. Conclusion: Synchronous liver resection, cytoreductive surgery and HIPEC is feasible in selected patients with low-volume CRPM and CRLM. Increasing PCI is associated with postoperative major morbidity, and should be considered during operative planning. Highlights: Synchronous liver resection, CRS and HIPEC has traditionally been contraindicated. Perioperative and survival outcomes of this procedure were evaluated on 23 patients. There was no mortality and major morbidity occurred in seven patients. Median DFS and OS was 18 and 37 months, respectively. Such management is safe and feasible in selected patients.